A nomogram for predicting axillary pathologic complete response in hormone receptor–positive breast cancer with cytologically proven axillary lymph node metastases. (25th July 2020) - Guo, Rong; Su, Yonghui; Si, Jing; Xue, Jingyan; Yang, Benlong; Zhang, Qi; Chi, Weiru; Chen, Jiajian; Chi, Yayun; Shao, Zhimin; Wu, Jiong
Abstract : Background: The objective of this study was to determine an axillary pathologic complete response (pCR) and its influencing factors in patients with hormone receptor (HR)–positive breast cancer and cytologically proven axillary lymph node metastases. A prediction nomogram was established to provide information for the de‐escalation of axillary management in these patients after neoadjuvant chemotherapy. Methods: The authors retrospectively enrolled all patients with HR‐positive breast cancer in the neoadjuvant chemotherapy data set of Fudan University Shanghai Cancer Center. All data were prospectively collected. From 2007 to 2016, 533 consecutive patients were included. Multivariate logistic regression analysis was performed, after which a nomogram was constructed and validated. Results: An axillary pCR was achieved in 168 patients (31.5%), the which was much higher than the proportion of those who achieved a breast pCR (103 patients; 19.3%). Patients who had human epidermal growth factor receptor 2‐positive disease ( P = .004), a better primary tumor response ( P = .001), earlier clinical stage ( P = .045), and lower estrogen receptor expression ( P < .001) were more likely to achieve a lymph node pCR. The nomogram indicated an area under the receiver operating characteristic curve (AUC) of 0.84 (95% CI, 0.78‐0.89) in the training set. The validation set showed good discrimination with an AUC of 0.75 (95% CI, 0.69‐0.81). The C‐index was 0.834 and 0.756 in the training and validation cohort, respectively. The nomogram was well calibrated. Conclusions: The authors developed and validated a nomogram for predicting axillary pCR in patients with HR‐positive disease accurately by using clinicopathologic factors available before surgery. The model will facilitate logical clinical decision making and clinical trial design. Abstract : An axillary lymph node pathologic complete response is significantly more common than a breast pathologic complete response in patients with hormone receptor‐positive breast cancer. A prediction nomogram that will provide information for the de‐escalation of axillary management after neoadjuvant chemotherapy is described.